2023
DOI: 10.1177/2515690x231160191
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Seizures, Cognitive Deficits, and Brain Histopathology by Phytochemicals of Imperata cylindrica (L.) P. Beauv (Poaceae) in Acute and Chronic Mutant Drosophila melanogaster Epilepsy Models

Abstract: Imperata cylindrica is a globally distributed plant known for its antiepileptic attributes, but there is a scarcity of robust evidence for its efficacy. The study investigated neuroprotective attributes of Imperata cylindrica root extract on neuropathological features of epilepsy in a Drosophila melanogaster mutant model of epilepsy. It was conducted on 10-day-old (at the initiation of study) male post-eclosion bang-senseless paralytic Drosophila ( parabss1) involved acute (1-3 h) and chronic (6-18 days) exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…To alleviate epilepsy symptoms, researchers have investigated using Imperata cylindrica root extracts in a mutant Drosophila "para" gene model. The treated flies exhibited an inhibitory effect on voltage-gated sodium ion channels, which reduced inflammation and increased tissue repair in brain cells, confirming the extract's efficacy in treating epilepsy [117].…”
Section: Scn Epilepsy Imperatacylindricamentioning
confidence: 57%
See 1 more Smart Citation
“…To alleviate epilepsy symptoms, researchers have investigated using Imperata cylindrica root extracts in a mutant Drosophila "para" gene model. The treated flies exhibited an inhibitory effect on voltage-gated sodium ion channels, which reduced inflammation and increased tissue repair in brain cells, confirming the extract's efficacy in treating epilepsy [117].…”
Section: Scn Epilepsy Imperatacylindricamentioning
confidence: 57%
“…Moreover, epilepsy is a neurological disorder characterized by sensory-motor deficits and convulsions. It can have various causes, including gene mutations that encode ion channels in brain cells responsible for transmitting signals between neurons [117]. To alleviate epilepsy symptoms, researchers have investigated using Imperata cylindrica root extracts in a mutant Drosophila "para" gene model.…”
Section: Scn Epilepsy Imperatacylindricamentioning
confidence: 99%
“…Additionally, the plant extracts have shown other beneficial effects, such as antihypertensive actions and the regulation of lipid metabolism and tolerance to hypoxia, indicating a broad range of potential medicinal uses [16] . Studies conducted on a Drosophila melanogaster epileptic mutant model showed that extracts derived from Imperata cylindrica exhibited neuroprotective effects [22] . This finding indicates its potential application in neurological conditions.…”
Section: Imperata Cylindrica (Mao Gen)mentioning
confidence: 99%